Diabetic kidney disease: what we know so far - literature review - Kuczyński, Piotr; Marszałek, Anna; Choiński, Maciej; Wasiewicz-Ciach, Paulina; Marzec, Marcelina Teresa; Wydra-Rojek, Aleksandra; Łakoma, Aleksandra; Marzec, Weronika Zofia; Kutyła, Katarzyna; Mokot, Wojciech Jan (Quality in Sport, 2024)
Diabetic Kidney Disease (DKD) is a major complication of diabetes mellitus, affecting approximately 40% of diabetic patients and representing the leading cause of chronic kidney disease and end-stage renal disease (ESRD). This review delves into the pathogenesis, diagnosis, and therapeutic advancements in DKD. Key pathological mechanisms include hyperglycemia, oxidative stress, and inflammation. Modern treatments, such as SGLT-2 inhibitors and GLP-1 agonists, offer renoprotective benefits by improving endothelial function, reducing inflammation, and mitigating oxidative stress. The review also highlights the importance of timely initiation and optimization of therapies to slow DKD progression and explores new avenues such as epigenetic therapies and autophagy enhancement. Further research is needed to fully understand the long-term benefits and optimal use of these treatments in DKD management.